Narrative form - Keen, Suzanne (Palgrave Macmillan, 2003)
This handbook concisely introduces narrative form to advanced students of fiction. Beginning with a survey of major theorists and approaches, and using clearly defined terms,Narrative Formexplains critical vocabulary and offers a variety of strategies for analyzing the formal qualities of fiction. Keen suggests that interpretations of form can be effectively integrated with contemporary approaches to literature, including feminist, postcolonial, and cultural studies methodologies.Narrative Formshows how to use the language of formal analysis accurately and innovatively.